Analisis Strategi Penggunaan Digital Marketing dalam Meningkatkan Penjualan : (Studi Kasus pada UMKM Alfa di Kota Medan) - Torang Daud Panjaitan; Mohd. Nawi Purba; Ara Auza (Jurnal Bintang Manajemen, 2025)
Social media marketing expands market reach through platforms such as Instagram, Facebook, and TikTok, while video marketing displays products more attractively on TikTok, Instagram Reels, or YouTube to increase customer engagement. Social media analytics functions to analyze customer data, measure campaign effectiveness, and optimize promotional strategies to be more targeted. This research used a quantitative method with 100 samples from Medan Selayang District using the cluster sampling method. The research results show that social media marketing has a positive and significant effect on increasing sales (t-statistics 6.249 > 1.66, p-values ​​0.000), while video marketing has no significant effect (t-statistics 0.784 < 1.66, p-values ​​0.433). Social media analytics has a positive and significant influence (t-statistics 2.589 > 1.66, p-values ​​0.010). Adjusted R-Square of 0.482 shows that 48.2% of the variation in the increase in MSME sales is explained by these three variables, while 51.8% is influenced by other factors outside this research.